(untitled) (Bangladesh Journal of Botany, 2021)
To explore the relationship between the dry matter contents of potato tubers and metabolic enzymes, an experiment was designed. Ten individual indicators, including metabolic enzymes, could be reduced to 4 comprehensive indicators by using a principal component analysis. Using these 4 components as independent variables (X) and the dry matter content as the dependent variable (Y), the following linear regression equation was obtained: Y = ‒51.802 ‒ 1.022X5 ‒ 0.034X6 + 0.872X9 + 0.286X10 (R2 = 0.889, P = 0.012). In a comparison between the dry matter contents (22.74, 16.58 and 20.72%) calculated according to the equation and the measured value (22.96, 17.09 and 19.75%), the absolute error was < 1% and the estimation accuracy was > 95%. These results indicated that the linear regression equation can be used to predict accurately and quickly the dry matter contents during the tuber enlargement stage. Bangladesh J. Bot. 50(2): 253-259, 2021 (June)